Optimizing Performance and Recovery: Dry Needling of Myofascial Trigger Points in Sports Medicine - Słuchocka, Joanna; Lewalski, Tymon; Florczyk, Martyna; Płuciennik, Lidia; Lewalski, Oskar; Jeruć, Klaudia (Quality in Sport, 2026)
Background. Myofascial pain syndromes (MPS) and musculoskeletal disorders are common conditions that can impair athletic performance. Dry needling (DN), an invasive physiotherapeutic technique targeting myofascial trigger points (MTrPs), has gained increasing attention as a therapeutic intervention in sports medicine and rehabilitation. Aim. This review aims to synthesize current evidence regarding the neurophysiological mechanisms, molecular effects, and clinical applications of DN in the management of musculoskeletal disorders, with particular emphasis on sports-related conditions. Methods. A comprehensive review of randomized controlled trials, systematic reviews, meta-analyses, and experimental mechanistic studies published primarily within the last 20 years was conducted using electronic databases including PubMed, Scopus. Results. DN modulates nociception at many levels. Mechanical stimulation of MTrPs triggers a local twitch response, reduces spontaneous electrical activity (SEA) and pro-inflammatory mediators (substance P, CGRP, IL-1β), improves microcirculation, and activates descending inhibitory pathways while normalizing cortical excitability. Clinical studies demonstrate that DN reduces pain intensity, enhances range of motion, optimizes muscle activation patterns, and shortens time to return to sport in conditions like patellofemoral pain syndrome, lateral epicondylalgia, rotator cuff-related shoulder pain, and hamstring strain. Conclusions:. Dry needling is a safe and effective adjunctive intervention in sports medicine and musculoskeletal rehabilitation. When integrated with structured exercise therapy and load management strategies, it enhances functional recovery, reduces injury recurrence, and optimizes athletic performance. Future studies should focus on standardization of needling protocols, identification of patient-specific predictors of response, long-term outcomes, and integration with objective biomarkers of muscle and neural function.